Facile Synthesis of Bimetallic Au-Pt, Pd-Pt, and Au-Pd Nanostructures: Enhanced Catalytic Performance of Pd-Pt Analogue towards Fuel Cell Application and Electrochemical Sensing. (20th October 2015) - Dutta, Soumen; Ray, Chaiti; Sarkar, Sougata; Roy, Anindita; Sahoo, Ramkrishna; Pal, Tarasankar
Graphical abstract: Surfactant free, fast synthesis of noble metal based bimetallic electrocatalysts has been done under an aromaticity driven mild reaction condition. Highlights: Surfactant-free, fast synthetic approach for Au-Pt, Pd-Pt and Au-Pd nanostructures. It has originated from an aromaticity driven process. Au based bimetallics proceed via Au seed formation to attain core-shell structures. Co-reduction of Pt 4+ and Pd 2+ helps Pd-Pt alloy formation. Pd-Pt shows admirably high electrocatalytic performance among three bimetallics. Abstract: Thermodynamic control and aromaticity driven instantaneous reaction strategy co-jointly result in three noble-metal based bimetallic nanostructures (namely Au-Pt, Au-Pd and Pd-Pt) through a surfactant-free pathway. Non-aromatic hantzsch 2, 4-dihydropyridine ester (DHPE) is proposed here as a reducing agent and in turn through the acquirement of aromaticity, DHPE provides a general route for the fast synthesis of these bimetallic nanoparticles. The Au-M (M=Pd, Pt) nanostructures are of typically core-shell type structure where Au forms the core and the shell is made of either Pd or Pt. Overwhelmingly, the same synthetic strategy leads to the formation of alloy nanostructures for Pd-Pt. The growth kinetics, reaction mechanism as well as the morphology of the particles could be supported with the redox properties of the precursor salts. The well-recognized catalytic activity of both Pt and Pd has been capitalized here in Pd-Pt alloy particles, which bring synergistic effect to engender its highest electrocatalytic performance and stability towards ethylene glycol oxidation reaction in comparison to the other electrocatalysts (Au-Pd, Au-Pt and commercial Pt/C). In addition, as-synthesized highly electroactive material Pd-Pt becomes an electrochemical sensor for explosive 2, 4 dinitrotoluene (DNT) with an impressive limit of detection (LOD) of ∼0.82 μM.